Freedom to Marry’s Ladder of Clarity: Lessons from a Winning Campaign (That Is Not Yet Won) - Wolfson, Evan (Columbia Journal of Gender and Law, 2015)
Evan Wolfson: Thank you, Suzanne. Let me start where Heather started, picking up also on what Suzanne just said, that many of us on both panels so far and throughout the day have worked together, some for decades. We have laughed together and fought together for decades. And we’ve welcomed in, and had the benefit of new people coming in-the next waves of talent, such as many of you here today. That’s what really has led to the success that we celebrate today.